School Environment and Retention of Learners with Disabilities in Universal Primary Schools in Kasese District - Kyakimwa, Sarah; Muhammad, Tukur; Wanjala, Gidraf Joseph; Kimani, Wilson; Silaji, Turyamureeba; Eze, Val Hyginus Udoka (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study investigates the relationship between the school environment and the retention of learners with disabilities in Universal Primary Schools (UPS) within Kasese District, Uganda. Employing a descriptive research design integrating quantitative and qualitative methodologies, the study examines three main objectives: the impact of teacher support, school infrastructure, and school relationships on the retention of learners with disabilities. A total of 154 respondents, including teachers, head teachers, and pupils from six selected UPS, participated in the study. Data collection involved self-administered questionnaires, interviews, and focus group discussions. Findings reveal various home-related factors influencing the retention of learners with physical disabilities, such as poverty, negative parental attitudes, and lack of essential self-help skills training. Despite respondents indicating moderate levels of school attendance and retention for learners with disabilities, enrolment and retention rates remain significantly lower compared to non-disabled peers. The study underscores the need for collaborative efforts among government bodies, school administrators, teachers, parents, and other stakeholders to implement sustainable measures aimed at improving the school environment and enhancing retention for learners with disabilities.